Biomechanical Differences Between Japanese and American Professional Baseball Pitchers - Oi, Takanori (Orthop J Sports Med, 2019)
BACKGROUND: Although baseball injuries are common in both Japan and the United States, the majority of pitching injuries in Japanese players occur at the shoulder, whereas most pitching injuries in American players occur at the elbow. A biomechanical comparison between Japanese and American pitchers may help to identify the different injury mechanisms. HYPOTHESIS: Japanese pitchers produce greater shoulder kinetics whereas American pitchers generate greater elbow kinetics. Also, kinematic differences will be found between the 2 groups, including longer stride and greater lead knee flexion for Japanese pitchers. STUDY DESIGN: Descriptive laboratory study. METHODS: Biomechanical data for 19 Japanese professional baseball pitchers and an age-matched group of 19 American professional baseball pitchers were collected by use of a 3-dimensional, automated, high-speed optical motion capture system. Anthropometric, kinetic, and kinematic data for both groups were compared by use of t tests (P < .05). RESULTS: American pitchers were taller and heavier and generated greater ball velocity (38.1 ± 1.6 vs 34.7 ± 1.1 m/s; P < .001) than their Japanese counterparts. Most elbow and shoulder kinetic parameters, including elbow varus torque (99 ± 17 vs 86 ± 17 N·m; P = .018), were greater for American pitchers. However, when normalized by bodyweight and height, shoulder horizontal adduction torque was greater for Japanese pitchers (6.8% ± 1.0% vs 5.8% ± 1.1%; P = .005). Japanese pitchers had longer stride (86% ± 5% vs 82% ± 6% of height; P = .023), greater shoulder abduction at ball release (101° ± 8° vs 94° ± 9°; P = .014), and greater knee flexion after ball release (39° ± 18° vs 28° ± 14°; P = .039). Japanese pitchers also demonstrated greater shoulder internal rotation velocity, elbow flexion, and elbow extension velocity. CONCLUSION: Greater elbow varus torque may predispose American pitchers to greater risk of elbow injury. Japanese pitchers may have increased risk of shoulder injury due to greater normalized horizontal adduction torque and greater abduction angle. Japanese pitchers may be able to reduce their shoulder torque and risk of injury by shortening their stride, reducing their lead knee flexion, and decreasing their throwing arm abduction. CLINICAL RELEVANCE: Understanding anthropometric, kinetic, and kinematic differences between pitchers from the 2 countries may be of value to clinicians and coaches working to maximize performance of the pitchers while minimizing the risk of injury.